Return and volatility spillovers between Nigeria and selected stock markets: Evidence from a diagonal BEKK-AMGARCH model - Tari Moses Karimo; Abraham Ochoche; Ngozi Victor Atoi (West African Journal of Monetary and Economic Integration, 2022)
The study examines returns spillover, shock, and volatility transmission between Nigeria and selected global stock markets over the period January 2000 to August 2021 using a diagonal BEKK-AMGARCH model. Results show that the Nigerian stock market exhibits characteristics of inefficiency, as investors could consistently make gains higher than the market average. Also, the study observes a positive return transmission between Japan and Nigeria only, suggesting that, investors could benefit from diversification into Nigeria and Japan markets. Except for China and Hong Kong, volatility is relatively more sensitive to bad news indicating that negative information shock heightens market risk more than positive shock due to increased trading activities arising from speculation. The policy implication is that the Nigerian market is less developed and requires improvement in infrastructure/institution to become more developed and integrated to the rest of the world. Also, investors can hedge against loss in Japan by diversifying into Nigeria.
Keywords: G14; G15; 330; Return; information shock; spillover; stock market; transmission; volatility